The Effect Of Green Advertising And Green Product On Pucrhase Intention In Tumblr Bottle Products With Green Trust As An Intervening (Case Study On Sarjanawiyata University Students Tamansiswa ) - Devi Andriana; Ambar Lukitaningsih; Budi Setiawan (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the effects of green advertising and green products on purchasing intention toward tumbler products, with green trust as an intervening variable. Using a quantitative approach, data were collected from 131 respondents consisting of Sarjanawiyata Tamansiswa University students and the Yogyakarta community. The results show that green advertising has a negative and significant effect on purchase intention, while green products have no significant direct effect. However, green products significantly increase green trust, and green trust positively affects purchase intention. Green trust mediates the effect of green products, but not green advertising, on purchase intention. Keywords: Green Advertising; Green Product; Green Trust; Purchase Intention